Teenagers' moral advertising literacy in an influencer marketing context. Issue 1 (2nd January 2022) - Sweeney, Emma; Lawlor, Margaret-Anne; Brady, Mairead
Abstract: Teenagers are avid consumers of social media and also constitute attractive target audiences for influencer marketing (IM). Teenagers can perceive strong, parasocial relationships with influencers, frequently regarding them as being akin to a peer or a friend. Furthermore, influencer endorsements are observed to carry greater credibility and authenticity than traditional forms of advertising. This therefore raises questions about young consumers' discernment of, and critical evaluation of the overall appropriateness when influencers act as conduits of commercial messages on behalf of brands. This paper reports on a qualitative study of 29 teenagers aged 15–17 years. The aim was to explore the participants' moral advertising literacy, namely their evaluations of the fairness and appropriateness of IM. The findings indicate whilst the participants were critical and sceptical towards the practice of IM in general (i.e. their dispositional advertising literacy), they were positively disposed towards specific commercial content emanating from specific influencers, (i.e. their situational literacy), often on the basis of the parasocial relationship that was seen to prevail between influencer and follower. This study therefore illustrates a gap between the teenagers' moral AL in the context of IM in general, and a corresponding willingness to apply this critical reflection, to known influencers.